Artificial intelligence, the state-of-the-art in scientific editing - Christian, John; As’syifa, Salsa Billa; Widjaja, Felix Firyanto; Hamid, Agus Rizal Ardy Hariandy (Faculty of Medicine Universitas Indonesia, 2025)
[No abstract available]